ANALISIS PENGARUH MOTIVASI, KREATIVITAS DAN ETIKA BISNIS ISLAM TERHADAP KEBERHASILAN UKM MELALUI INOVASI SEBAGAI VARIABEL PEMODERASI DI SALATIGA - Nur Hikromah; Abdul Aziz Nugraha (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the success of UKM with the independent variables Creativity Motivation and Islamic Business Ethics with Innovation as a moderator variable in Salatiga.This research is a quantitative research with primary data, the population in this study is all UKM owners in Salatiga in 2022. The sampling technique in this study was simple random sampling, namely by randomly determining the sample of UKM actors in Salatiga.The data collection method was carried out using questionnaires and interviews conducted with UKM in Salatiga in 2022. The data obtained was then processed using the IBM SPSS Statistics version 22 tool. The analysis carried out included instrument tests, classic assumption tests, statistical tests and MRA tests. The results in this study show that motivation has a positive but not significant effect on the success of UKM, creativity has a positive and significant effect on the success of UKM, Islamic Business Ethics has a positive and significant effect on the success of UKM and innovation is not proven to be a moderator variable or does not moderate motivation, creativity and business ethics. Islam on the success of UKM.